The production of biodiesel by algae: integration with shrimp farming - Jeronimo, Carlos Enrique de Medeiros; Silva, Rafael Mariano Dantas; Bacholsky, Richard Guimarães (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Biodiesel production in the world and has grown steadily along its technologies. Natural resources are plentiful, however there is some difficulty in the extraction of these biomass resources, in most cases financial. One of these is the algae that even having an exponential potential for the generation of biodiesel, finds a huge bottleneck on the cost of it. There are at least four recovery mechanism biodiesel have been addressed but the two most used on the market, which consists of open ponds (Raceway Pounds) systems and bioreactors system. Applicability to both the reuse of effluents from shrimp farming. Water features were addressed in a clear and biodiesel from algae were also covered reporting of their quality and the commercial purpose as required by the National Petroleum Agency.